The Relation Between Knowledge and Experience of Facing Flood Toward The Anxiety Level of Head Families in The Flood-Prone Areas - Fitriani, Dwi Rahmah; Milkhatun, Milkhatun; Damaiyanti, Mukhripah; Muflihatin, Siti Khoiroh; Rizal, Alfi Ari Fakhrur (South East Asia Nursing Research, 2019)
Families who reside in the surrounding flood-prone areas require flood preparedness to undertake preparedness so that family members do not create new problems such as anxiety. This study aims to determine the relationship of knowledge with experience in dealing with the level of anxiety of household head anxiety. This research is a cross-sectional descriptive correlation study and the sample used in this study is 225 households. The results of the study using the Anova test showed that the knowledge and experience of dealing with floods were related to the anxiety of household heads in disaster-prone areas (p = 0.001; α = 0.05). Multivariate of results were found that the most related factor was an experience. This study recommends that the family knowledge needs to be increased through simulation training to deal with floods by involving the Regional Management Agency, the local government and the Public Health Center